Male description of the phytotelma-dwelling species Polypedilum parthenogeneticum (Chironomidae: Chironominae) - Donato, Mariano Humberto (2019)
The male of the phytotelma-dwelling species Polypedilum parthenogeneticum is described from Eryngium L. (Apiaceae) (Corrientes province, Argentina) and is included within the subgenus Polypedilum. The pupal diagnosis is emended, its geographic distribution is updated, and their taxonomic relationships with other Neotropical species of Polypedilum are discussed.